Spatial organization of palmitoyl acyl transferases governs substrate localization and function. (1st January 2019) - Philippe, Julie M.; Jenkins, Paul M.
Abstract: Protein palmitoylation is a critical posttranslational modification that regulates protein trafficking, localization, stability, sorting and function. In mammals, addition of this lipid modification onto proteins is mediated by a family of 23 palmitoyl acyl transferases (PATs). PATs often palmitoylate substrates in a promiscuous manner, precluding our understanding of how these enzymes achieve specificity for their substrates. Despite generous efforts to identify consensus motifs defining PAT-substrate specificity, it remains to be determined whether additional factors beyond interaction motifs, such as local palmitoylation, participate in PAT-substrate selection. In this review, we emphasize the role of local palmitoylation, in which substrates are palmitoylated and trapped in the same subcellular compartments as their PATs, as a mechanism of enzyme-substrate specificity. We focus here on non-Golgi-localized PATs, as physical proximity to their substrates enables them to engage in local palmitoylation, compared to Golgi PATs, which often direct trafficking of their substrates elsewhere. PAT subcellular localization may be an under-recognized, yet important determinant of PAT-substrate specificity that may work in conjunction or completely independently of interaction motifs. We also discuss some current hypotheses about protein motifs that contribute to localization of non-Golgi-localized PATs, important for the downstream targeting of their substrates.